CHOLESTEROL RATE AND IMMUNE SYSTEM INDICES IN PEOPLE WITH SYMPTOMS OF VEGETATIVE-VASCULAR DYSTONIA, WHO LIVED IN THE TERRITORIES CONTAMINATED WITH RADIONUCLIDES - Sokolenko, V.L. (World of Medicine and Biology, 2016)
We evaluated the link between cholesterol level and immune system indices in people with symptoms of vegetative-vascular dystonia syndrome who lived in contaminated areas. It is determined that total cholesterol level reaches maximum homeostatic value within this group. At the same time lymphocytes are slightly activated, but the effect is accompanied by inhibition of differentiation processes of functionally mature T lymphocytes. Specific immunity dysfunction is to some extent compensated by growth of granulocytic cells in the background of decrease in activity of professional phagocytes.
Keywords: cholesterol; vegetative-vascular dystonia; radiation; immunity